2012
DOI: 10.1001/archfacial.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cleft Width in Clefts of Secondary Palate on the Risk of Velopharyngeal Insufficiency

Abstract: Objective To investigate the association between velopharyngeal insufficiency (VPI), a common finding after cleft palate repair, and various risk factors, including cleft width.Methods We performed a retrospective cohort study of patients with isolated cleft palates repaired from 2003 to 2008 at a tertiary children's hospital. Patients were observed postoperatively for development of VPI and palatal fistula. The primary risk factor was cleft width. Covariates included cleft length, age at surgery, and presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Lam and colleagues (2012) showed that a value higher than 10 mm for b1 was associated with an increased incidence of velopharyngeal insufficiency. Their cases were repaired with a Furlow double-opposing Z-plasty or a combined Furlow palatoplasty and a V to Y pushback procedure.…”
Section: Discussionmentioning
confidence: 98%
“…Lam and colleagues (2012) showed that a value higher than 10 mm for b1 was associated with an increased incidence of velopharyngeal insufficiency. Their cases were repaired with a Furlow double-opposing Z-plasty or a combined Furlow palatoplasty and a V to Y pushback procedure.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies 23,24 have assessed similar outcomes and associations with preoperative cleft widths. In 2009, Parwaz et al 23 found that a width of 15 mm or greater was significantly associated with risk of fistula.…”
Section: Discussionmentioning
confidence: 98%
“…The remaining 59 articles reported a fistula rate but did not specify if PSIO was used. Twenty-six of these were excluded because the contact details of the corresponding authors were not available (Furlow, 1986; Amaratunga, 1988; Horswell et al, 1993; Senders and Sykes, 1995; Emory et al, 1997; Wilhelmi et al, 2001; Sie and Gruss, 2002; Helling et al, 2006; Ravishanker, 2006; Hassan and Askar, 2007; Andrades et al, 2008; Bindingnavele et al, 2008; Khosla et al, 2008; Steinbacher et al, 2011; Dong et al, 2012; Lam et al, 2012; Tan et al, 2012; Jackson et al, 2013; Mahoney et al, 2013; Nadjmi et al, 2013; Butow et al, 2014; Lithovius et al, 2014; Pan et al, 2014; Yamaguchi et al, 2016; Mann et al, 2017; Murthy et al). An additional 27 articles were excluded because the corresponding authors did not respond to our request to obtain the necessary data (Padwa and Mulliken, 2003; Jackson et al, 2004; LaRossa et al, 2004; Inman et al, 2005; Mak et al, 2006; Ogata et al, 2006; Kobus, 2007; Phua and de Chalain, 2008; Agrawal, 2009; Sullivan et al, 2009; Ezzat et al, 2010; Lu et al, 2010; Paniagua et al, 2010; Isik et al, 2011; Losken et al, 2011; Williams et al, 2011; Eberlinc and Kozelj, 2012; Rauf et al, 2012; Black and Gampper, 2014; de Agostino Biella Passos et al, 2014; Deshpande et al, 2014; Zhang et al, 2014; Hudson and Pickett, 2015; …”
Section: Resultsmentioning
confidence: 99%